THE COMPLEMENTARY THERAPY USED FOR HYPERTENSION: A SYSTEMATIC REVIEW - Rumbo, Helmi; Rasiman, Noviany Banne; Betan, Yasinta (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction: Hypertension is the most dominant risk factor for cardiovascular disease, which is the most frequent cause of deaths all over the world. Patients’ hypertension requires non pharmacological interventions as an integral part of case management. Complementary and alternative medicine (CAM) are recognized and accepted in several countries that have developed a high degree of modern medicine; some researchers showed that CAM could be recommended for lowering blood pressure. The aim of this study is to explore the most popular method of CAM used for hypertension.Method: A systematic review was conducted by searching online databases between 2012 - 2022, by using PRISMA 2020 protocol in filtering the articles. Articles were sourced from Elsevier, Plos One, NIH, Lancet, BMC, Sage, Springer, Wiley, Lippincott and Garuda.  The researcher obtained 26 articles for final review, with inclusion criteria people with hypertension that use CAM as a therapy to prevent elevated blood pressure. Results: Eleven articles were RCT, seven articles were experiments, three articles were descriptive, three articles were cross sectional, one article was cohort, and one article was case control. The result showed that the CAM was effective in lowering blood pressure. People with hypertension most often used herbal medicine, acupuncture, acupressure, yoga, meditation, tai chi, reflexology, massage, guided imagery, and aromatherapy oil (in sequentially). Conclusions: Perception/belief, lack of information, experience and culture affect people's behavior in choosing medical drugs over CAM. Therefore, health care should promote CAM and provide patients with non-pharmacological intervention.